2000
DOI: 10.1097/00003226-200007000-00024
|View full text |Cite
|
Sign up to set email alerts
|

High-risk Corneal Allografts Are Capable of Stimulating Complement Dependent Cytolytic Antibodies

Abstract: Allospecific corneal antibody may be involved in corneal graft rejection in high-risk donor-host combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Ocular immune privilege, however, can be compromised under certain conditions with corneal transplantation. A previous study reported that allospecific complement‐dependent cytolytic Abs may be involved in the rejection of corneal allotransplantation . Increased C3a levels in the AH are a biomarker related to corneal xenograft rejection .…”
Section: Discussionmentioning
confidence: 97%
“…Ocular immune privilege, however, can be compromised under certain conditions with corneal transplantation. A previous study reported that allospecific complement‐dependent cytolytic Abs may be involved in the rejection of corneal allotransplantation . Increased C3a levels in the AH are a biomarker related to corneal xenograft rejection .…”
Section: Discussionmentioning
confidence: 97%
“…In corneal allotransplantation, a CD4 + T cell-mediated reaction is primarily involved in graft rejection [8,[61][62][63], while CD8 + T cell-and complement-mediated reactions are partially involved in allograft rejection [64][65][66][67].…”
Section: Rejection Mechanism In Corneal Xenotransplantation Through Vmentioning
confidence: 99%
“…However, the rejection can be CD8 T-cell mediated in CD4 knockout mice [25,26]. In addition, some reports have suggested a possible involvement of allospecific antibodies in corneal graft rejection, in a complement-dependent manner [27,28].…”
Section: Rejection Mechanism In Xenocorneal Transplantationmentioning
confidence: 99%